Quality indicators assessing antibiotic use in the outpatient setting: a systematic review followed by an international multidisciplinary consensus procedure. (6th June 2018) - Le Maréchal, Marion; Tebano, Gianpiero; Monnier, Annelie A; Adriaenssens, Niels; Gyssens, Inge C; Huttner, Benedikt; Milanič, Romina; Schouten, Jeroen; Stanić Benić, Mirjana; Versporten, Ann; Vlahović-Palčevski, Vera; Zanichelli, Veronica; et al.
Abstract: Objectives: Quality indicators (QIs) assessing the appropriateness of antibiotic use are essential to identify targets for improvement and guide antibiotic stewardship interventions. The aim of this study was to develop a set of QIs for the outpatient setting from a global perspective. Methods: A systematic literature review was performed by searching MEDLINE and relevant web sites in order to retrieve a list of QIs. These indicators were extracted from published trials, guidelines, literature reviews or consensus procedures. This evidence-based set of QIs was evaluated by a multidisciplinary, international group of stakeholders using a RAND-modified Delphi procedure, using two online questionnaires and a face-to-face meeting between them. Stakeholders appraised the QIs' relevance using a nine-point Likert scale. This work is part of the DRIVE-AB project. Results: The systematic literature review identified 43 unique QIs, from 54 studies and seven web sites. Twenty-five stakeholders from 14 countries participated in the consensus procedure. Ultimately, 32 QIs were retained, with a high level of agreement. The set of QIs included structure, process and outcome indicators, targeting both high- and middle- to low-income settings. Most indicators focused on general practice, addressing the common indications for antibiotic use in the community (particularly urinary and respiratory tract infections), and the organization of healthcare facilities. Twelve indicators specifically addressed outpatient parenteral antimicrobial therapy (OPAT). Conclusions: We identified a set of 32 outpatient QIs to measure the appropriateness of antibiotic use. These QIs can be used to identify targets for improvement and to evaluate the effects of antibiotic stewardship interventions.